Prevalence and Factors Associated With Intimate Partner Violence Among Women in Haiti: Understanding Household, Individual, Partner, and Relationship Characteristics - Occean, James R. (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) is a significant public health issue with detrimental consequences for women’s reproductive, mental, and physical health. In Haiti, IPV is a major obstacle to women’s development. Yet, the determinants of IPV victimization are still not well understood. In this study, we utilized the 2016–2017 Haiti Demographic and Health Survey to determine the prevalence of IPV victimization and its subtypes (emotional, physical, and sexual abuse) among married or cohabiting women (N = 3,805) of reproductive age (15–49) by their current husband/partner. Logistic regression was conducted to explore the association between IPV and household, individual, husband/partner, and relationship characteristics. The prevalence of IPV victimization was 32.5% with the majority reporting emotional (24.7%) followed by physical (16.8%) and sexual (10.5%) violence. Increased odds of IPV victimization were found among women with children in the household (adjusted odds ratio [AOR] = 1.45, 95% confidence interval [CI] = [1.03, 2.02]), with attitudinal acceptance of wife-beating (AOR = 1.45, 95% CI = [1.05, 2.02]), and those who witnessed their father beating their mother (AOR = 1.49, 95% CI = [1.18, 2.67]). Higher odds of reporting IPV victimization were also found among women whose partner drank alcohol (AOR = 2.89, 95% CI = [2.29, 3.65]), who were in a polygynous relationship (AOR = 1.76, 95% CI = [1.23, 2.40]), and displayed one or more controlling behaviors (AOR = 1.92, 95% CI = [1.42, 2.59]). Women who reported being afraid of their partner had greater odds of IPV victimization (AOR = 16.22, 95% CI = [8.38, 31.39]). Decreased odds of reporting IPV were associated with women living in rural areas (AOR = 0.73, 95% CI = [0.53, 1.00]) and those unmarried, but living with their partner (AOR = 0.62, 95% CI = [0.43, 0.90]). Our findings identify subgroups of women in Haiti that may be vulnerable to IPV victimization. Thus, we recommend a differentiated approach to IPV prevention strategies and interventions that consider women’s family structure in the household as well as individual, partner, and relationship characteristics.